(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article addresses participatory management in schools, focusing on consolidating democracy and ethics in the educational environment. The central proposal is to discuss how democratic principles and ethical values can be incorporated into school management practices, promoting a culture of participation, dialogue, and shared responsibility among the different subjects that make up the school community. The research was developed through a qualitative, bibliographical approach, using contemporary authors and recent scientific productions addressing educational management, professional ethics, and social participation in the school context as a basis. The study reveals that, although there are legal provisions that encourage the democratization of school management, such as councils and assemblies, structural, cultural, and formative challenges persist that limit the effective participation of the school community in decision-making processes. The results indicate that participatory management contributes to strengthening more respectful interpersonal relationships, developing a more welcoming institutional environment, and increasing collective engagement around pedagogical objectives. Ethics, in turn, emerges as a guiding principle for educational and administrative practices, being fundamental to building a school environment based on justice, respect for diversity, and the appreciation of dialogue. The analysis also highlights that ongoing training for administrators and the creation of effective listening spaces are essential elements for consolidating effective democratic management. It is concluded that the integration of democracy and ethics in school management is indispensable for promoting a quality public school, focused on developing critical, participatory citizens committed to social transformation.